Improving Ship Crew Job Satisfaction: The Role of Work Environment and Career Development - Rumopa, Michael; Baharuddin, Baharuddin; Halik, Johannes Baptista; Lambe, Kristian Hoegh Pride (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to examine the influence of the work environment and career development on the job satisfaction of Yihai ship crews under Raffles Ship Management Pte Ltd. Given the unique and challenging nature of maritime work, both factors are considered crucial in shaping crew satisfaction. A quantitative approach was employed using a survey method, with data collected from 35 ship crew members selected through purposive sampling. The data were analyzed using Structural Equation Modeling (SEM) with the SmartPLS 4.0 software. The results revealed that the work environment did not have a significant impact on job satisfaction. Conversely, career development showed a positive and significant influence. When assessed simultaneously, both variables contributed meaningfully to job satisfaction. These findings underscore the importance of prioritizing structured and ongoing career development programs to enhance employee welfare and satisfaction. For Raffles Ship Management Pte Ltd, this study provides valuable insights for formulating effective policies aimed at boosting the motivation, performance, and long-term retention of their ship crews.